Consummation through Twin Suicides in Ibsen - Anwar, Nadia Anwar (Journal of Research in Humanities, 2023)
In the course of literary criticism, various critics have been analyzing the socio-economic and psychological dimensions of the theme of suicide in Ibsen’s plays. In the present study of Ibsen’s Rosmersholm (1886) and When We Dead Awaken (1899) the same theme has been explored from a different angle in order to reveal those provocative hidden motives that make an individual embrace death so willingly. Consequently, suicide does not remain a selfdestructive act but a means to achieve union with one’s soul mate. By committing twin suicides the true couples of the plays i.e., Rosmer, Rebecca and Rubek, Irene reach the zenith of consummation, where the concept of suicide as an impulsive mental condition is negated. Rather it becomes a hermit like reclusive state of mind, when all the corporeal desires and worldly distractions become meaningless and the glories of a peaceful existence of the world hereafter manifest themselves to the ones who happily give away their lives for it. Putting together the fragments of their memories, these characters eventually enable themselves to approach an integrated vision which in their perception leads them to success but to the world may seem an utter failure resulting in their fruitless deaths.